'Shi Han Quan' natural soda water prevents development of gout. (30th October 2017) - Zhao, Qingsong; Wang, Lipei; Wu, Xiongbin; Liu, Tingting; Xu, Jinmei; Li, Ming; Li, Bo; Guo, Min; Cheng, Zhifeng
Abstract: Purpose: This study aimed to explore the regulatory mechanism of the natural soda Shi Han Quan (SHQ) in the development of gout. Methods: Human umbilical vein endothelial cells (HUVECs) were stimulated with monosodium urate (MSU) for 24 h to induce acute gouty inflammation in vitro . HUVECs were divided into four groups: ddH2 O group, ddH2 O + MSU group, 1/2 ddH2 O +1/2 SHQ + MSU group, and SHQ + MSU group. The effects of SHQ on cell viability, concentration and expression of intercellular adhesion molecule‐1 (ICAM‐1), and MSU‐induced release of interleukin (IL)‐1β and IL‐6 were investigated. Additionally, cell viability and ICAM‐1 concentration and expression were detected after HUVECs were incubated with the culture supernatant of THP‐1 cells that had been treated with phorbol 12‐myristate 13‐acetate (PMA), MSU and SHQ for 24 h. Results: The viability of HUVECs was significantly decreased with increasing transfection concentrations of MSU, and MSU treatment resulted in a significant increase of the concentration and expression of ICAM‐1. In addition, SHQ improved the MSU‐induced decrease in cell viability and alleviated MSU‐mediated increase in ICAM‐1 levels. Moreover, SHQ decreased MSU‐induced release of IL‐1β and IL‐6. After HUVECs were incubated with the culture supernatant of THP‐1 cells that had been treated with PMA, MSU and SHQ for 24 h, SHQ also markedly alleviated the effects of MSU, such as by increasing cell viability and decreasing ICAM‐1 levels. Conclusions: Drinking natural soda water may have a significant role in preventing gouty inflammation.